STRATEGI PENGEMBANGAN USAHA GARAM RAKYAT (PUGAR) DI DESA LABUHAN BONTONG KABUPATEN SUMBAWA - Darussalam, Marzuki; Fitriyani, Ika; Sumbawati, Novi Kadewi (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the strategy to determine the Strategy for Developing People's Salt Business in Labuhan Bontong Village, Sumbawa Regency. This type of research is descriptive qualitative research. The data used in this study are primary data and secondary data. The tool used to collect data is by using interviews. The informants in this study are key informants consisting of 15 informants. The data analysis technique is by using SWOT analysis. The results of the study showed that the Internal and External factors of communities salt production business in Labuhanan Bontong Village, Sumbawa Regency had unbalanced value, namely the internal factor was 4.35 and the external factor was 4.37 with strength value was 2.20, weaknesses was 2.15 and opportunities was 2.67 and threats was 1.70. Based on the results of the SWOT matrix analysis, 8 alternatives were obtained with selected strategic priorities, namely supporting aggressive policies (growth-oriented strategy) that can be carried out by utilizing existing strengths and opportunities to overcome weaknesses and threats faced. The alternative strategies that can be carried out in developing the people's salt business (PUGAR) in Labuhan Bontong Village include increasing the quality and quantity of production results by utilizing technological advances, and utilizing programs organized by the government to improve the quality of farmers' human resources.